Design and application of a real-time monitoring system for vessel motion and sea environment. Issue 7 (25th June 2021) - Han, Duanfeng; Huang, Kuo; Zan, Yingfei; Yuan, Lihao; Wu, Zhaohui; Kang, Dongchun
Abstract: Engineering vessels play an important role in offshore engineering operations, and the control of their motion under the effects of sea environments is crucial for the safety and efficiency of the operation. In this study, a real-time monitoring system for vessel motion and sea environment with synchronization function designed at the Harbin Engineering University is introduced. The system consists of four modules responsible for vessel motion monitoring; sea environment monitoring; synchronous data acquisition and transmission; and data processing, storage, and display. These modules work together to achieve real-time monitoring of the vessel motion and position, as well as environmental loads, including waves, sea currents, and winds. The system is applied and tested during the installation of a dummy pipeline end termination (PLET) at the shipboard in the Liuhua gas field. The application is described in detail and the monitoring results are presented and analyzed in the time domain. The monitoring system is confirmed to be suitable for various offshore engineering operations, and the monitoring results can provide important verification for numerical simulations of those operations.